The Performance of Forestry Extension Functional Officials in the Ministry of Environment and Forestry - Yulita, Ita; Djamil, Masyhudzulhak; ., Indupurnahayu (Jurnal Manajemen, 2018)
Workload, problem management and task completion in forestry are the work entrusted to the Forestry Extension Workers. In the highly complex condition of forestry problems, Forestry Extension Workers are needed to bridge and outline the problems and to prevent the emergence of deeper, more widespread and prolonged problems. The problems served as the background for the writer to conduct the study in the thesis completion in the Master of Management Program. The problems are related to the effects of competence, compensation and career development factors of the Forestry Extension Workers working in the Ministry of Environment and Forestry and the performance expected to achieve the completion of forestry extension works. The data analysis used to explain the effects of competence, compensation and career development and the performance of Forestry Extension Workers was the Structural Equation Model (SEM) with Smart PLS. Based on the estimations and t-values, it can be concluded that the exogenous variables of compensation and career development affect the endogenous latent factor of the performance of Forestry Extension workers (?), whereas competence has no effect on the performance of Forestry Extension Workers.